Comparing intentional vocabulary learning strategies of rote-copying vs read-plus - Wong, Sze Wei (2013)
The purpose of this within-group experimental study was to compare the effectiveness of two explicit vocabulary learning strategies (VLS) of Rote-Copying (RC) and Read-Plus (RP) treatment on vocabulary acquisition and retention among English as a second language (ESL) learners at lower secondary school level in Malaysia. Participants were 35 Form 1 students with low level English proficiency who participated in both treatments for two weeks with each treatment carried out once in each week. A posttest was administered a week after the treatments. Participants read adapted texts and underwent different treatments. The RC required participants to copy L2 words, sentence in context and its translated L1 counterparts twice; while three vocabulary enhancement activities were used in RP. Nation’s 1000 Level Vocabulary Test was used in this study. Results indicate that there was no significant difference between RC and RP in vocabulary learning. Both treatments lead to significant vocabulary learning. However, participants showed better vocabulary gain after undergoing the RP treatment in the pottest. Interview finding indicated that participants preferred the more cognitively-challenging RP treatment. In contrast, the RC was deemed boring and ineffective. Nevertheless, RC is useful for low proficient ESL learners. In sum, intentional VLS are the key to vocabulary learning.